Sistem Inovasi Kiai Dalam Membangun Strategi Keberhasilan Pondok Pesantren Salafiyah Di Provinsi Jambi - Hifasoh, Fikri; Latif, Mukhtar; Rosyadi, Kemas Imron (Universitas Pahlawan Tuanku Tambusai, 2024)
This article is presented as an initial step to build an academic program with the aim of meeting the critical needs of Santri Salafiyah Islamic boarding schools in Jambi Province have an important role in the preservation and development of traditional Islamic religious education. However, the challenges of modernization and social change demand innovation to ensure the success and sustainability of these educational institutions. This study examines the innovation system applied by Kiai as leaders of Salafiyah Islamic boarding schools in developing success strategies. Using a qualitative approach, this study explores the innovative methods used by Kiai in managerial, curriculum, and human resource development aspects. The results show that adaptation to technology, renewal of teaching methods, and community-based management are key elements in the pesantren's success strategy. The innovations applied by Kiai not only improve the quality of education but also strengthen the competitiveness and relevance of pesantren in the context of modern times. This research provides insights for other pesantren managers in designing and implementing effective strategies to succeed in traditional Islamic education.